OP63 Very early workplace sickness absence interventions: A systematic review and meta-analysis of their effectiveness. (13th September 2016) - Demou, E; Vargas-Prada, S; Lalloo, D; Avila-Palencia, I; Sanati, K; Sampere, M; Freer, K; Serra, C; Macdonald, EB
Abstract : Background: Sickness absence (SA) remains a significant problem globally, notably in developed countries. Early intervention to enhance return to work has been identified as a key priority in disability and SA management and these interventions implemented in the early stages of SA episodes indicate that 'early' and 'very early' intervention may result in a quicker return to work and be cost-effective. The objective of this systematic review is to investigate the effectiveness of 'very early' (under 15 days) SA workplace interventions to enhance return to work. Methods: A systematic literature search was conducted in Pubmed, HMIC, Cochrane library database, CINAHL, PsychInfo and Embase. Study selection, quality appraisal and data extraction were carried out by independent pairs of researchers using pre-established criteria. Randomised controlled trials, controlled trials, cluster-randomised trials, cross-over designs, before and after studies and interrupted time-series published in English until September 2014 were included if they assessed the effectiveness of workplace interventions to reduce SA in workers who were on sick leave no longer than 15 days. Primary outcome measures included rates of and time until RTW, productivity loss, and recurrences of SA. The Cochrane Collaboration tool was used to assess the risk of bias. Results: We found limited available evidence on the benefits of 'very early' workplace interventions in terms of RTW after a SA episode compared to usual care. Only three randomised controlled trials classed as high or intermediate quality were identified. Early part-time sick leave together with appropriate job modifications led to a reduction on the duration and recurrence of SA, and increased self-perception of health and quality of life. There is evidence of benefit of intervening during the first two weeks of SA for musculoskeletal disorders and less for workers with mental health problems. Conclusion: Our review identified a lack of substantive evidence from the literature at this time point to support 'very early' intervention compared to usual care. Consensus is required on the definition of 'early' and 'very early' interventions and further research is recommended to improve understanding of the factors influencing when and how best to intervene for maximum gain.